Primary Cultures of Glomerular Parietal Epithelial Cells or Podocytes with Proven Origin - Kabgani, Nazanin; Grigoleit, Tamara; Schulte, Kevin; Sechi, Antonio; Sauer-Lehnen, Sibille; Tag, Carmen; Boor, Peter; Kuppe, Christoph; Warsow, Gregor; Schordan, Sandra; Mostertz, Jörg; Chilukoti, Ravi Kumar; et al. (PLOS ONE, 2012)
Parietal epithelial cells (PECs) are crucially involved in the pathogenesis of rapidly progressive glomerulonephritis (RPGN) as well as in focal and segmental glomerulosclerosis (FSGS). In this study, transgenic mouse lines were used to isolate pure, genetically tagged primary cultures of PECs or podocytes using FACsorting. By this approach, the morphology of primary glomerular epithelial cells in culture could be resolved: Primary podocytes formed either large cells with intracytoplasmatic extensions or smaller spindle shaped cells, depending on specific culture conditions. Primary PECs were small and exhibited a spindle-shaped or polygonal morphology. In the very early phases of primary culture, rapid changes in gene expression (e.g. of WT-1 and Pax-2) were observed. However, after prolonged culture primary PECs and podocytes still segregated clearly in a transcriptome analysis - demonstrating that the origin of primary cell cultures is important. Of the classical markers, synaptopodin and podoplanin expression were differentially regulated the most in primary PEC and podocyte cultures. However, no expression of any endogenous gene allowed to differentiate between the two cell types in culture. Finally, we show that the transcription factor WT1 is also expressed by PECs. In summary, genetic tagging of PECs and podocytes is a novel and necessary tool to derive pure primary cultures with proven origin. These cultures will be a powerful tool for the emerging field of parietal epithelial cell biology.